The Role of Sustainable Entrepreneurship in Advancing the United Nations Sustainable Development Goals: Themes, Challenges, and Opportunities - Mirmohammad Seyednouri; Ali Farzpourmachiani; Simin Naghibi Masouleh; Saeed Najafi; Adel Safaei; Mohammadali Rajabi Torbehbar; Mehdi Farzpourmachiani (Pandawa Institute, 2026)
Sustainable entrepreneurship entrepreneurial action that simultaneously pursues economic viability, social inclusion, and ecological integrity has moved from a niche scholarly domain to a central lever for achieving the United Nations Sustainable Development Goals (SDGs). This review synthesizes conceptual and empirical research on how sustainable entrepreneurship advances the SDGs, identifying dominant themes, mechanisms of impact, challenges, and opportunity spaces. We connect foundational theory on opportunity recognition under ecological and social constraints with contemporary work on circular economy ventures, impact investing, blended finance, and impact management standards. We further examine how national policy frameworks and ecosystem-level interventions (e.g., UNCTAD’s Entrepreneurship Policy Framework, the EU Social Economy Action Plan, and UNDP’s SDG Impact Standards) can enable entrepreneurs to contribute more effectively to SDG targets. The review surfaces persistent obstacles measurement and attribution of impact, financing gaps for early-stage and inclusive ventures, institutional voids, trade-offs and mission drift, and uneven scaling pathways while outlining promising research and practice opportunities in business model innovation for the SDGs, inclusive and frugal innovation, and outcome-aligned capital. We conclude with a research agenda and policy implications to accelerate entrepreneurship-led progress toward 2030.